Early Management of Hyperuricemia Might Delay the Development of Essential Hypertension - Sultana, Sabera; Rahman, Arifur; Kabir, Farhana; Yasmin, Ayesha; Sultana, Rabeya (KYAMC Journal, 2021)
Background: In the 21st century, the prevalence pattern of hypertension in different developing countries differs from developed countries. Persistent hypertension is one of the risk factors and is the leading cause of heart disease, chronic kidney disease (CKD) & cerebrovascular disease. Even mild to moderate essential hypertension usually causes significant renal function impairment only after several years. Objectives: To assess the serum uric acid level in hypertensive patients and compare the findings with those found in normotensive people. Materials & Methods: This case-control study was done at the Department of Biochemistry, Mymensingh Medical College, Mymensingh during the period of January 2010 to December 2010. A total of 143 subjects of both sexes were selected for the purpose. Out of them, 73 were the case and 70 were the control. The subjects were classified into the following groups; Group I includes 73 were essential hypertensive subjects. Group II includes 70 were healthy adults. All statistical parameters analysis were done by SPSS 12.0 version; P-value<0.05 was considered as significant. Results: There was a significant (P<0.05) increase in blood urea in subjects with hypertension compared to that of the control. Conclusion: Evaluation of uric acid before and during treatment of hypertension is required to identify as a risk factor. KYAMC Journal. 2021;12(3): 117-121